Edaravone dexborneol protects cerebral ischemia reperfusion injury through activating Nrf2/HO‐1 signaling pathway in mice. (4th May 2022) - Xu, Lili; Gao, Yaran; Hu, Ming; Dong, Yanhong; Xu, Jing; Zhang, Jiawei; Lv, Peiyuan
Abstract: Stroke is the leading cause of disability and death. When blood flow is restored after prolonged ischemia and hypoxia, it leads to excessive production of reactive oxygen species (ROS), increased local inflammation, and apoptosis, which are the cause of most cerebral ischemia reperfusion injury (CIRI), leading to secondary brain tissue damage. Edaravone dexborneol is a novel neuroprotective agent consisting of edaravone and borneol. Studies have shown that it has synergistic antioxidant and anti‐inflammatory effects. However, whether Edaravone dexborneol stimulates the Nrf2/HO‐1 pathway to regulate NADPH oxidase 2 (NOX2) remains unclear. In this study, wild‐type (WT) mice and Nrf2 knockout (KO) mice were used to investigate the antioxidant, anti‐inflammatory, and anti‐apoptotic effects of Edaravone dexborneol on CIRI and its mechanism. The cognitive function of mice was evaluated with the Morris water maze (MWM), test and the cell structures of hippocampus were observed by hematoxylin and eosin (H&E) staining. Nrf2, HO‐1, and NOX2 proteins and apoptosis‐related proteins Bcl‐2, Bax, and Caspase 3 were detected by western blotting. Nrf2, HO‐1, NOX2, and inflammatory factors TNF‐α, IL‐1β, IL‐4, and IL‐10 were detected by real‐time polymerase chain reaction. The results showed that Edaravone dexborneol treatment improved learning and memory performance, neuronal damage, and enhanced antioxidant, inflammation, and apoptosis in CIRI mice. In addition, Edaravone dexborneol induced the activation Nrf2/HO‐1 signaling pathway activation while inhibiting NOX2 expression. Overall, these results indicate that Edaravone dexborneol ameliorates CIRI‐induced memory impairments by activating Nrf2/HO‐1 signaling pathway and inhibiting NOX2.